A Pornography Literacy Class for Youth: Results of a Feasibility and Efficacy Pilot Study. Issue 1 (2nd January 2018) - Rothman, Emily F.; Adhia, Avanti; Christensen, Tiffany T.; Paruk, Jennifer; Alder, Jessica; Daley, Nicole
ABSTRACT: The purpose of this study was to evaluate the preliminary efficacy of a media literacy curriculum focused on pornography among a sample of U.S-based, urban-residing youth. Participants were 24 youth between the ages of 15–24 years old, although 65% were 17–18 years old. The sample was 43% female, 43% male, 9% transgender, 52% Black, 22% Hispanic, 13% other race, 64% heterosexual, 14% gay, lesbian or bisexual, and 18% other sexual orientation. Participants completed a pre-test prior to the first class session and a post-test after the fifth and final session. Pornography-related knowledge increased from pre- to post-test. A change in the anticipated direction was observed for some pornography-related attitudes, and some pornography-related behavioral intentions. Pornography-related behavior (e.g., seeking out pornography for the first time) did not change from pre- to post-test. The novelty of these findings are two-fold. First, the study demonstrated that it is feasible to implement a pornography literacy curriculum in a nonschool setting, and second, that this particular curriculum may have had some positive impact.